EVALUATION OF THE USE OF ANTIDIABETIC DRUGS IN PATIENTS WITH DIABETES MELLITUS TYPE 2 (TWO) IN THE INPATIENT INSTALLATION OF THE MATARAM CITY GENERAL HOSPITAL IN 2021 - Meri Alpian (Scientia Integritas Utama, 2022)
This study aims to determine the use of drugs in Diabetes Mellitus (DM) Type 2 patients in the Inpatient Installation of the Mataram City Regional General Hospital in 2021. This study is an observational non-experimental study using a descriptive analysis design and retrosfective data collection. This study was conducted by analyzing the medical record data of patients with a sample of 85. The results obtained showed that the use of the drug in patients with Diabetes Mellitus (DM) Type 2 most used single insulin lantus (33%), and combination insulin apidra with lantus (28.2%). The least used single insulin is apidra (2.3%). The least used combination insulin is sansulin with novoravid (1.1%) and lantus with novoravid (3.5%). The most widely used oral antihyperglycemia drug is metformin (25.9%). Glimepiride (4.7%) and pioglitazone (1.1%). The results of the Drug Related Problem (DRP) evaluation obtained 10 cases with details: 3 indications of no drugs, 1 improper choice of drugs, 2 no indications of drugs, 1 dose of drugs too large (over dosing), 1 undesirable drug reaction, and 2 drug interactions.